Collection of nasal secretions and tears and their use in allergology. Issue 1 (February 2018) - Castelli, Sveva; Arasi, Stefania; Pawankar, Ruby; Matricardi, Paolo M.
Abstract : Purpose of review: The identification of immunological markers in nasal secretions and tears is becoming essential in the study of allergic diseases. The collection procedure of nasal and ocular secretions directly influences the results, thus it is of paramount importance to validate and standardize the sampling process. Recent findings: Current techniques for nasal secretions sampling are mainly based on three principles: collection of spontaneous secretions, nasal washings, and absorption. Collection of spontaneous secretions is appropriate in subjects with nasal hypersecretion, whereas in healthy individuals the collected volume is frequently insufficient. Nasal washings are associated with an unpredictable, high dilution and concentrations of markers often fall below detection limits of immunological assays. Absorption seem to provide the best compromise between sufficient sample amounts and detectability of inflammatory mediators and immunoglobulin E. Tear samples can be obtained by glass capillary tubes, filter paper strips and ophthalmic sponges. Volumes are however small or highly diluted through reflex tearing. Summary: Secretions reflect the local inflammatory activity and provide valuable information about the immunological reaction to allergens at the target organ. There is increasing evidence of the potential clinical role of their analysis, for diagnosis, and monitoring of allergic rhino-conjunctivitis. Appropriate collection and processing is very important and requires special attention.